Optimising 'Lambe Hoaks' Digital Literacy to Strengthen National Resilience Against Hoaxes - Putra, Fadhil A.; Samad, M. Yusuf; Mulyadi (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: The spread of hoaxes has intensified in recent years, posing a threat to national resilience due to their potential to incite national disintegration. This study aims to optimise the